Repeat staging laparoscopy for gastric cancer after preoperative therapy. Issue 1 (7th June 2018) - Thiels, Cornelius A.; Ikoma, Naruhiko; Fournier, Keith; Das, Prajnan; Blum, Mariela; Estrella, Jeannelyn S.; Minsky, Bruce D.; Ajani, Jaffer; Mansfield, Paul; Badgwell, Brian D.
Abstract : Background and Objectives: Staging laparoscopy is recommended before preoperative therapy in patients with locoregional gastric cancer, but yield of repeated diagnostic laparoscopy at the time of resection is unknown. Methods: Retrospective review of a prospective database of patients with gastric adenocarcinoma (1994‐2016) who had negative staging laparoscopy followed by preoperative therapy and subsequent attempted resection. Primary outcome was positive exploration (peritoneal or unresectable disease) at the time of resection. Multivariable logistic regression identified factors associated with positive exploration. Results: Of the 451 patients with attempted resection, 54 (12.0%) had positive explorations, including 48 with peritoneal disease. Patients with positive explorations were more likely to be female and have poorly differentiated tumors, linitis features, and signet‐ring morphology. There was no significant difference by exploration results in age, race, clinical stage, or delayed definitive surgery. Positive explorations were independently associated with poor differentiation (OR 4.6, 95%CI 1.4‐15.3; P  = 0.01) and linitis (OR 4.2, 95%CI 1.9‐9.2; P  < 0.001). Positive explorations were seen in 14.0% of patients with poor differentiation, 36.6% of patients with linitis, and 5.8% of patients with neither linitis nor poor differentiation. Conclusion: Despite negative pretreatment laparoscopy, post‐treatment repeat laparoscopy may prevent non‐therapeutic laparotomies. At a minimum, we recommend selective repeat laparoscopy for patients with linitis features.